2019
DOI: 10.1128/mra.01336-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Bacteriocin-Producing Streptococcus thermophilus Strains ST106 and ST109

Abstract: Streptococcus thermophilus strains ST106 and ST109 produce broad-spectrum bacteriocins encoded within a bacteriocin-like peptide (blp) gene cluster. This study reports the complete genome sequences for both strains, with the ST109 chromosome containing 1,788,866 nucleotides (nt) and 1,572 predicted genes, and ST106 having 1,856,083 nt and 1,601 predicted genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Finally, the pan genome of the species is not closed yet, suggesting that sequencing of additional strains will be important. Certain new complete genomes have appeared in the databases since the initiation of our analysis (Proust et al, 2018;Renye et al, 2019), but more are required to further expand and validate any lineage-like patterns that may exist and could be related to the technological/probiotic repertoire of S. thermophilus.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the pan genome of the species is not closed yet, suggesting that sequencing of additional strains will be important. Certain new complete genomes have appeared in the databases since the initiation of our analysis (Proust et al, 2018;Renye et al, 2019), but more are required to further expand and validate any lineage-like patterns that may exist and could be related to the technological/probiotic repertoire of S. thermophilus.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of strains ST106 ( Renye et al, 2019a ) and B59671 ( Renye et al, 2017 ) were completely sequenced in previous studies. Analysis of the RNA-seq data was performed using Geneious Prime software (Biomatters Inc., Boston, MA, United States) and by Igenbio Inc. using their proprietary ERGO 2.0 platform.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the bacteriocins produced from S. thermophilus , called thermophilins, are encoded by the bacteriocin-like peptide ( blp ) gene cluster. Strains B59671 ( Gilbreth and Somkuti, 2005 ; Renye and Somkuti, 2013 ), ST106 ( Somkuti and Renye, 2014 ; Renye et al, 2019a ; Figure 1A ), LMD-9 ( Fontaine et al, 2007 ; Fontaine and Hols, 2008 ), ST109 ( Renye et al, 2019b ), and ST118 ( Somkuti and Renye, 2014 ) all produce bacteriocins encoded within the blp cluster. The blp -encoded bacteriocins produced by ST106 and B59671 are called thermophilin 106 and thermophilin 110, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis of LMD-9 revealed that BlpD alone was sufficient to inhibit the growth of most target bacteria, with BlpU, E, and F identified as accessory peptides that broaden the activity spectrum of BlpD ( Fontaine and Hols, 2008 ). The presence of BlpD in strains ST106 and ST109 suggests it is also the primary bacteriocin within these strains ( Somkuti et al, 2015 ; Renye et al, 2019 ). Additional variations within this gene cluster have been reported ( Rossi et al, 2013 ), and more may arise as the number of fully sequenced strains of S. thermophilus increases.…”
Section: Introductionmentioning
confidence: 99%